Estimation of Encounter Rate and Population Structure of Ungulates by Using Vehicle Road Transects in Ranthambore National Park, India - Lahkar, Dipankar (Indian Forester, 2015)
Encounter rate and group composition of chital (Axis axis), sambar (Cervus unicolor), nilgai (Boselaphus tragocamelus), wild pig (Sus scrofa) and chinkara (Gazella bennetti) were studied in the Ranthambhore National Park, Rajasthan, India during 2010-2011. 93.65 Km vehicle road transect was done to conduct the study. The encounter rate of chital (3.91) was found highest followed by sambar (1.29). The average group size of chital (3.36±0.866) was also found highest followed by sambar (1.70±0.37) and nilgai (1.31±0.46). The ratio of young to adult females was found highest in wild pig (71.42: 100 females), followed by sambar (12.60:100 females) and chital (11.8: 100 females). The ratio of number of adult male to adult females was found highest in sambar (49.30: 100 females) followed by nilgai (31.42:100 females). However, the adult female ratio constituted the main bulk of all ungulates population. The road transect was found to be an effective way for the continuous monitoring of the ungulate population in the park and can be implemented as a rapid assessment technique.